Frequency Selective Surface With Two Quasi-Independent Notch Frequencies - Ladislau Matekovits; Aldo De Sabata; Alndrei-Marius Silaghi (IEEE Access, 2019)
A double-layer frequency selective surface (FSS) built on FR4 substrate exhibiting two notch frequencies in the 0-10-GHz range is introduced. Recently published examples demonstrate that further research needs to be undergone for obtaining separate tuning of the resulted notch frequencies. Thus, this issue is addressed in this paper: the notch frequencies can be quasi-independently set by appropriate values given to the geometrical parameters of the two metal patterns in the unit cells of the structure. The FSS behavior is stable with respect to the angle of incidence of impinging electromagnetic waves up to 45°, as proved by simulation and validated by experiments.